Enhancing Sulh Application in Real Estate Property Claims in Malaysian Syariah Courts: (Pemerkasaan Pelaksanaan Sulh dalam Kes Tuntutan Hartanah Orang Islam di Mahkamah Syariah di Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2021)
Sulh (settlement) has been used in Malaysia as an alternative to the litigation process since 2002. The Syariah courts face several challenges in carrying out sulh. The main cause of this challenge is limited jurisdiction in addition to other administrative issues. The present study was conducted with the objective to analyse the method of application of sulh concerning real estate in the Syariah courts. This study also suggests improvements to improve the application of sulh for case resolution in the Syariah courts. This is a qualitative study, whereby data was collected through library research and interviews with parties directly involved in the sulh process. The data collected, such as case judgments and interviews, was analysed using a descriptive content analysis. This study found that problems concerning the sulh process are the result of administrative issues, while legal challenges and limited jurisdiction do not have much impact on sulh implementation. This is because the courts use their discretion and implement sulh with flexibility in line with laws and regulations, as well as existing sulh procedures where necessary. Much depends on the commitment and skills of sulh officers who are trained and knowledgeable in legal and case management aspects. To avoid a clash between the rules and discretionary practices, some improvement measures are required. These improvements involve the revision and coordination of existing laws and sulh regulations. An implication of this this study is that it can help strengthen the application of sulh in matters concerning real estate in the Syariah courts, especially with the said improvements.Keywords: sulh, real estate, Syariah Courts